Travel Choice Component: Is The Price Important For Open Trip Tourists? - Ika B. Suryaningsih, Kristian S. W. Nugraha, Deny K. Moelyadi (Jurnal Manajemen, 2020)
This study aims to prove the role of price moderation in the travel choice component, namely the relationship of destination, accommodation, travel companions, and duration of open trip travel choice. The sample used was 120 tourists who travelled using an open trip package. The analysis in this study is a structural equation model (SEM-PLS) with a moderating effect using the SMARTPLS 03 software. The results showed that the destination, travel companion, and duration variables significantly influence travel tour choices. The accommodation has a negative coefficient but does not have a significant effect on travel choice. The price moderation coefficient also affects the strengthening of the relationship of destination, travel companions, and duration with travel choice. However, price moderation weakens the bond between accommodation and travel options.